Extension of holomorphic mappings for several moving hypersurfaces - Si Duc Quang (Український математичний журнал, 2012)
We prove the big Picard theorem for holomorphic curves from a punctured disk into P ⁿ(C) with n + 2 hypersurfaces. We also prove a theorem on the extension of holomorphic mappings in several complex variables into a submanifold of P ⁿ(C) with several moving hypersurfaces.